Low field magnetoelectric studies on sol–gel grown nanostructured YMnO3 manganites. (March 2018) - Joshi, Zalak; Dhruv, Davit; Rathod, K.N.; Boricha, Hetal; Gadani, Keval; Pandya, D.D.; Joshi, A.D.; Solanki, P.S.; Shah, N.A.
Abstract: Single phasic nanostructured YMnO3 manganites were successfully synthesized by employing acetate precursor based modified sol–gel technique followed by their sintering at different temperatures. Structural studies were carried out by performing X–ray diffraction (XRD) measurement and Rietveld analysis on raw data of XRD. Particle size and shape were studied using transmission electron microscopy (TEM) while size distribution was investigated by performing particle size analyzer. Nanostructured samples were studied for their electrical properties under low applied magnetic field of 1.2T. Frequency and magnetic field dependent dielectric behavior has been understood on the basis of boundaries between the particles and inverse Dzyaloshinskii–Moriya (DM) interaction. Nanostructured YMnO3 manganites exhibit positive magnetodielectric (MD) effect. Universal dielectric response (UDR) model and relaxation mechanism have been employed for dielectric behavior of the samples understudy. Role of particle morphology and magnetic disorder have been discussed for the understanding of impedance and negative magnetoimpedance (MI) of the samples. Frequency and magnetic field dependent variation in conductivity has been explained using boundary and magnetic disorders and free charge carriers in the samples. All nanostructured YMnO3 show positive Magnetoconductivity (MC) throughout the frequency and magnetic field range studied. Variation in voltage dependent hysteretic capacitance and estimated built–in potential have been discussed in the context of the role of defects, vacancies, disorder and free charge carriers in the samples sintered at different temperatures.